Does Leverage Impact the Choice of Financing in Cross-Border Mergers and Acquisitions? Evidence from Emerging Economies - Akanksha Jain; Smita Kashiramka,; Sonali Jain (American Business Review)
Cross-border mergers and acquisitions (CBMA), as an internationalization strategy, have been used by firms from emerging economies to attain competitive advantage at a global level. However, little attention has been paid to capital structure decisions in CBMA, carried out by firms in these economies. The study disentangles this relationship between the acquirer’s capital structure and the financing method used during the course of mergers and acquisitions (M&A) in an international setting. It is a novel attempt to examine the moderating effect of acquirer size on the relationship between leverage and financing method in the acquisition offer. The study utilizes 1817 cross-border deals undertaken by 20 emerging economies from 2009 to 2021. The key findings suggest that highly leveraged acquirers are more likely to have stock in their offer as compared to the cash component. Contrary to expectations, size and liquidity have a negative effect on the choice of financing. Further, a disaggregated analysis examines the impact of the financial system of the acquirer country and the development status of the target country on the method of payment. The implications of the capital structure and payment choices are abundant for various stakeholders -policymakers, managers, and the board of directors involved in CBMA.